Cuidados de enfermagem nas complicações da punção venosa periférica em recém-nascidos - Modes, Priscilla Shirley Siniak dos Anjos (2011)
The aim of this work was to analyze nursing care in the prevention and treatment of complications of peripheral venipuncture in newborns hospitalized in Neonatal Intensive Care Units. It is a descriptive exploratory study, with qualitative approach conducted with nurses who cared for newborns in hospitals in Cuiaba, Mato Grosso, Brazil. Data were collected by means of semi-structured interviews and analyzed according to thematic analysis’ technique. Preventive measures for complications mentioned by respondents were: appropriate choice of vein puncture, observation of the infusion, careful administration of medications and access withdrawal. To treat complications the professionals use warm and cold compresses with sodium bicarbonate, venous access removing, anti-inflammatory ointment, papain and bandage on the puncture area. The results showed that many nursing professionals perform preventive and treatment care without scientific basis. As a consequence, the results are ineffective. The data suggest the need for improvement of the nursing staff concerning intravenous therapy.